Pengaruh Profitabilitas Terhadap Kinerja Keuangan PT Bank Central Asia Tbk Terdaftar di Bursa Efek Indonesia Periode 2021-2024 (Jurnal Riset Manajemen dan Akuntansi, 2025)
The objective of this study is to evaluate the impact of return on investment on the company's financial performance as measured by PT Bank Central Asia Tbk's price to book value for the period 2021-2024. In this research, a quantitative approach using simple regression analysis is applied. The data used are the financial statements of Bank Central Asia. The results of this study show that profitability has no significant effect on financial performance.